2011
DOI: 10.4103/1319-3767.84483
|View full text |Cite
|
Sign up to set email alerts
|

Use of the platelet count/spleen diameter ratio for the noninvasive diagnosis of esophageal varices in patients with schistosomiasis

Abstract: Background/Aim:In patients with liver cirrhosis, the platelet count/spleen diameter ratio has been validated as a parameter for the noninvasive diagnosis of esophageal varices. Schistosoma infection is a frequent cause of portal hypertension in Middle Eastern countries, and is associated with the development of esophageal varices. In this study we aimed to evaluate the platelet count/spleen diameter ratio as a noninvasive tool for the prediction of the presence of esophageal varices in patients with schistosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Agha et al [ 23 ] found that median platelet count (82,000 vs 172,000/μL; P < 0.0001) in cirrhotic patients correlated with the presence or absence of EV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Agha et al [ 23 ] found that median platelet count (82,000 vs 172,000/μL; P < 0.0001) in cirrhotic patients correlated with the presence or absence of EV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…2 papers [ 10 , 20 ] were published in abstracts and 47 papers were full-texts. The etiologies of cirrhosis were alcohol, schistosomiasis, and viral hepatitis in 1 [ 12 ], 2 [ 5 , 32 ], and 13 [ 9 , 19 , 22 , 26 , 27 , 30 , 33 , 36 , 39 , 40 , 42 – 44 ] papers, respectively. Two papers were about EV and GV [ 8 , 12 ], and the rest of the papers were about EV alone.…”
Section: Resultsmentioning
confidence: 99%
“…Majority (45.0%) of patients in the series had medium size EV followed by 27.0% had small and 19.0% patients had large EV. Agha et al 12 showed 72.0% patients had endoscopic evidence of EV. In this study, EV were found in more patients may be due to late presentation of the patients to the hospital.…”
Section: Discussionmentioning
confidence: 98%
“…Agha et al 12 found that platelet count/spleen diameter ratio <885 had 100% sensitivity (89-100, 95% confidence interval [CI]), 92% specificity (62-99, 95% CI), 12.0 positive likelihood ratio, and 0.01 negative likelihood ratio for the diagnosis of EV. Accuracy of the platelet count/spleen diameter ratio cut-off value as evaluated by the c-index was 0.989 (95% CI 0.897-0.992).…”
Section: Discussionmentioning
confidence: 99%